The Cairo Conference of 1943 Roosevelt, Churchill, Chiang Kai-shek, and Madame Chiang - Heiferman, Ronald (McFarland & Co., Publishers, 2011)
"This historical book chronicles the Cairo Conference, the events leading up to the conference, and the consequences of the decisions, understandings, and misunderstandings that took place at the summit. This text examines the enormous impact the conference had on the course of the war in Asia and post-war Sino-Western relations"--Provided by publisher.